Peran Mahasiswa Dalam Menegakkan Hukum di Indonesia - Nadia Sandi Rahmah; Sasmi Nelwati (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
The role of students in enforcing the law in Indonesia has become an increasingly important topic in recent years. This article aims to explore the contribution of students in encouraging compliance with the law, as well as to analyze the impact of their role on the legal system in Indonesia. This research uses a qualitative approach by conducting in-depth interviews and document analysis to gain an in-depth understanding of the role of students in enforcing the law. This study examines the impact of student activism, legal education, and community involvement in shaping the legal landscape in Indonesia. By analyzing the contributions and challenges faced by students in law enforcement, this article highlights the important role of students in advancing the rule of law and ensuring justice in Indonesian society. It is hoped that the results of this research will provide valuable insight for related parties in understanding the contribution of students in strengthening law enforcement in Indonesia.